Pesquisa, desenvolvimento e caracterização de comprimidos contendo entacapone, carbidoba e levodopa - Rodovalho, Luciana Ferreira Fonseca (2012)
Entacapone is a catechol-o-methyl transferase inhibitor used in association with carbidopa and L-dopa in the treatment of Parkinson’s disease. Currently, only one medication containing the association of these three substances is available on the market and it is under patent protection. The objectives of this study were the development and the physicochemical characterization of tablets containing the association of entacapone, carbidopa, and L-dopa using Stalevo® as a reference medication. The evaluation of possible incompatibilities between entacapone, carbidopa, L-dopa, and the excipients was carried out as a preformulation step. To achieve this, initially, differential scanning calorimetry (DSC) analyses were performed and, posteriorly, additional confirmatory studies were conducted using Fourier transformation-infrared spectroscopy (FTIR) and optical microscopy. The tablets were developed using the wet granulation method and the wet granulation method in a high shear mixer and physicochemical parameters were evaluated both for the granulate (moisture, density, and flow) and the oral dosage forms developed (friability, hardness, average weight, disintegration, and content of active ingredient). The dissolution profile of the tablets obtained was assessed based on Stalevo®. Tablets containing entacapone should contain pharmacotechnical elements to promote its bioavailability, since it presents low solubility and low permeability. Therefore, for the development of tablets, different batches were produced using surfactants. Entacapone associated with carbidopa, magnesium stearate, and crospovidone presented signs of degradation, according to FTIR and microscopy. Thus, these excipients should be avoided in the development of solid dosage forms containing entacapone. The batches of core tablets developed during this study were approved regarding the physicochemical criteria, including the dissolution profile. The coated tablets containing poloxamer 407 presented dissolution profile similar to the reference medication.